Medication-Related Problems Across The Continuum Of Care In Hospital-Acquired Infections: A Disease-Based Clinical Review (The Review of Diabetic Studies, 2024)
Hospital-Acquired Infections (HAIs) are a significant healthcare issue worldwide that has caused significant morbidity and mortality in patients, extended hospitalization, and increased healthcare expenditures. Antimicrobial resistance, biofilm-related pathogens, invasive medical equipment, and a high incidence of medication-related issues (MRP) throughout the continuum of care are increasing the complexity of HAIs management. These issues are usually caused by improper antimicrobial use, dose, drug-drug interactions, adverse drug reactions, and medication reconciliation issues in case of care transitions. Biofilm forming organisms like Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter baumannii also play a bigger role in compromising the treatment efficacy since it decreases the antimicrobial penetration and enhances tolerance and resistance. The present review presents a disease-focused approach to clinical pharmacy on MRPs that take place pre-admission (before admission), in hospital (during hospitalization), transitions of care (acute care), and post-discharge in patients with HAIs. It emphasizes the importance of clinical pharmacists in the identification, prevention, and resolution of the MRPs using antimicrobial stewardship programs, therapeutic drug monitoring, medication reconciliation, deprescribing strategies, and educating patients. Interventions by pharmacists have continued to show decreases in adverse drug events, prescribing of incorrect medications, antimicrobial misuse, readmission, and cost of healthcare and have also led to better clinical outcomes and patient safety. The emerging challenges are also included in the review, such as environmental-driven resistance factors, like the microplastics and the hospital wastewater, and the perspectives in the future, which includes the implementation of precision medicine, fast-diagnosis, and artificial intelligence-based decision making. The main idea to improve the antimicrobial therapy, decrease MRPs and enhance the outcomes of patients with hospital-acquired infections is strengthening clinical pharmacy services across the continuum of care.